Brewing Legal Times : Things, Form, and the Enactment of Law - Grabham, Emily (Book collections on Project MUSE., 2016)
"Much socio-legal scholarship assumes that even if experiences of law and time differ, people and laws exist within an overarching, shared time-frame. In Brewing Legal Times, Emily Grabham boldly departs from this assumption, drawing on perspectives from actor-network theory, feminist theory, and legal anthropology to advance our understanding of law and time. Grabham argues that human, material, and legal relationships constantly generate new temporalities because of human and nonhuman interactions. By engaging with the creative potential of "things" such as cells, viruses, reports, legal documents, and more, our understanding of law and time is subject to change. In challenging the scholarship on the materiality of time and law, Brewing Legal Times encourages us to confront the multiple and mundane ways in which time is enacted through legal networks."--